New criteria of serviceability of aerodrome lighting equipment - Ванецян, С. Г.; Ванецян A. C. (Proceedings of National Aviation University (archive), 2000)
Analyzed are the criteria of lighting equipment serviceability of various categories of aerodromes according to the materials of normative technical documentation of Ukrainian and Russian civil aviation and recommendations of ICAO. Proposed are new substantiated criteria of lighting equipment serviceability of various categories, under different atmospheric conditions which are based on recommendations and standards ICAO adapted to the conditions of new criteria in Ukraine. The advantages and correctness of new criteria are proved by calculation of reliability of imported modem lighting equipment by means of the worked out criteria